Pengenalan Simulasi Jaringan Local Area Network Menggunakan Aplikasi Cisco Packet Tracer bagi Siswa/i SMK Swasta Mulia Pratama Medan - Murdani , Murdani; Sembiring, Abdul Sani (Fakultas Ilmu Komputer, Universitas Katolik Santo Thomas Medan, 2023)
SMK Swasta Mulia Pratama Medan is one of the teacher training high schools in the city of Medan that has the determination to become a superior institution and become a reference in learning innovation. in the implementation of education carried out for the concentration of networks in SMK Swasta Mulia Pratama Medan, specifically studied practice and theory in class and laboratory on a scheduled basis, but it turns out that the lessons delivered in class and laboratory are still felt to be lacking due to limited time and facilities in the laboratory itself, where the LAN network application module taught must be studied in groups alternately and this is a real obstacle for students who queue to learn LAN network tools and modules. The use of network simulation software is very important to facilitate the abstraction of Computer Network subjects. In the study, the impact and effectiveness of network simulators in the teaching and learning process of computer networks will be examined. The network simulator chosen is Cisco Packet Tracer